An approach to mitigate denial of service attacks in ieee 802.11 networks - Ribeiro, Adriano Cesar [UNESP]; Pinto, Alex Sandro Roschildt [UNESP]; Zafalon, Geraldo Francisco Donega [UNESP]; Pigatto, Daniel Fernando; Branco, Kalinka Castelo; Cansian, Adriano Mauro [UNESP] (Science Publications, 2014)
Wireless networks are widely deployed and have many uses, for example in critical embedded systems. The applications of this kind of network meets the common needs of most embedded systems and addressing the particularities of each scenario, such as limitations of computing resources and energy supply. Problems such as denial of service attacks are common place and cause great inconvenience. Thus, this study presents simulations of denial of service attacks on 802.11 wireless networks using the network simulator OMNeT++. Furthermore, we present an approach to mitigate such attack, obtaining significant results for improving wireless networks.
Keywords: Computer Networks; Security; Denial of Service Attacks; Embedded Systems